Natural selection contributes to the myopia epidemic. Issue 6 (17th August 2020) - Long, Erping; Zhang, Jianzhi
Abstract: The prevalence of myopia, or nearsightedness, has skyrocketed in the past few decades, creating a public health crisis that is commonly attributed to lifestyle changes. Here we report an overall increase in the frequencies of myopia-associated mutant alleles over 25 years among participants of the UK Biobank. Although myopia itself appears to be selected against, many of the mutant alleles are associated with reproductive benefits, suggesting that reproduction-related selection inadvertently contributes to the myopia epidemic. We estimate that, in the UK alone, natural selection adds more than 100 000 myopia cases per generation, and argue that antagonistic pleiotropy be broadly considered in explaining the spreads of apparently disadvantageous phenotypes in humans and beyond. Abstract : Analysis of the UK Biobank shows that the rapid increase in the prevalence of myopia is in part attributable to positive selection for myopia-associated risk alleles due to antagonistic pleiotropy.